2017
DOI: 10.1021/acssynbio.7b00261
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium glutamicum Chassis C1*: Building and Testing a Novel Platform Host for Synthetic Biology and Industrial Biotechnology

Abstract: Targeted top-down strategies for genome reduction are considered to have a high potential for providing robust basic strains for synthetic biology and industrial biotechnology. Recently, we created a library of 26 genome-reduced strains of Corynebacterium glutamicum carrying broad deletions in single gene clusters and showing wild-type-like biological fitness. Here, we proceeded with combinatorial deletions of these irrelevant gene clusters in two parallel orders, and the resulting library of 28 strains was ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 53 publications
4
48
0
1
Order By: Relevance
“…The determined PIs are in good agreement with numerous previous reports (cf. Table S1, Supporting Information), proving that the presented workflow is suitable to replace laborious shake flask or bioreactor experiments for standard growth phenotyping.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The determined PIs are in good agreement with numerous previous reports (cf. Table S1, Supporting Information), proving that the presented workflow is suitable to replace laborious shake flask or bioreactor experiments for standard growth phenotyping.…”
Section: Resultssupporting
confidence: 92%
“…The two genome‐reduced strains carrying the largest gene cluster deletions, PC1_NprE and PC1_53_NprE, showed no significant differences in growth and cutinase production compared to the wild type (Table ). These findings are consistent with previous results, where the background strains (without expression plasmids) showed no differences in defined and enriched CGXII medium . Hence, it can be concluded that there is no observable interaction between the products of deleted genes and cutinase secretion, i.e., all deleted genes could be classified as irrelevant for this purpose.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…While the first artificial genomes were basically copying natural genomes, new approaches aimed at genome reductions to design the optimal minimal cell (“ model chassis ”) for biotechnological production systems. Examples are Mycoplasma mycoides JCVI‐syn3.0 (Hutchison et al ) which has a 50% reduced genome size compared to M. mycoides , the “Minibacillus” with a 36% reduced genome size compared to wildtype Bacillus subtillis (Reuß et al ), or Corynebacterium glutamicum with 13.4% genome reduction (Baumgart et al ). From here, synthetic biology moved on to engineer yeast (Richardson et al ) and mammalian (Martella et al ) artificial chromosomes.…”
mentioning
confidence: 99%